PENERAPAN TAX PLANNING MELALUI DEDUCTIBLE DAN UNDEDUCTIBLE EXPENSE PADA PT.HALUAN NATURA, MEDAN - Elidawati; Niken Cristian Ng; Sunarji Harahap (JURNAL BISNIS KOLEGA, 2022)
PT.Haluan Natura, Medan is a company engaged in the tire trade. The phenomenon that occurs in company is that company carry out fiscal reconciliation before tax reporting. However, the company does not do tax planning first, as a result there are costs that should be used as deductible expense instead it must be corrected because it is still included in the undeductible expense category. This study uses quantitative descriptive methods, namely describing the problems that occur by using quantitative data from financial statements. The results showed that the fiscal reconciliation at PT.Haluan Natura, Medan included corrections to donations that were not in accordance with tax regulations, corrections to allowances that were not included in the income tax component of article 21, corrections to depreciation costs on assets used for certain positions, and correction of bank interest income and bank interest tax.  Keywords: Tax Planning, Deductible, Undeductible Expense.